United Kingdom : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation reports that the United Kingdom's economic recovery has been sluggish, as the needed hand-off from public to private demand-led growth has not fully materialized. Economic activity is projected to gain modest momentum in future, but the pace of expansion is expected to be weak relative to the scale of underutilized resources. Executive Directors have welcomed the authorities' efforts aimed at economic rebalancing. However, they have cautioned that a stalling recovery, high unemployment, and uncertain external conditions continue to present significant challenges.